Predators Show Seasonal Predilections for Model Clay Spiders in an Urban Environment - Mason, L.; Wardell-Johnson, Grant; Luxton, S.; Bateman, Bill (Nature Publishing Group, 2018)
Predator-prey interactions may be altered under human-induced rapid environmental change, such as urbanisation. Extensive clearing in urban areas may leave short-range endemic species, such as mygalomorph spiders, more vulnerable to local extinction through predation in remaining remnants. Predation rates on Australian mygalomorph spiders were assessed using clay models of two size classes (5 cm, 3 cm), during two time periods in 2016 (January–February, July–August). Size and phenology of models resembled the mygalomorph genera Aname and Teyl occurring in these local urban remnants. Local predator guilds were significantly influenced by leaf-litter cover (%) and proportion of surrounding parkland. Preference for spider vs. control models was consistent across all predator types (bird, rodent, lizard and wasp), but specialist spider wasps (Pompilidae) only attacked spider models. Generalist predators (birds, lizards and rodents) were more opportunistic. Lizards and rodents exhibit similar predation behaviour, indicating there may be some inter-specific competition. Invasive generalists (e. g. rodents) or urban adapters (e. g. corvids) are more likely to represent an increased threat to spiders than are co-evolved specialists (e.g. spider wasps).